Ray’s Werewolf social life deducting Card-game for learning purposes : Kartu Permainan Werewolf Ray untuk Pembelajaran - Yulianto, Raysandi; Fediyanto, Niko (Universitas Muhammadiyah Sidoarjo, 2026)
This study presents General Background on the growing integration of game-based learning in English as a Foreign Language classrooms to support communicative competence. Specific Background highlights the need for interactive media that encourage high school students to practice speaking in authentic and low-anxiety contexts. Despite various digital and traditional game applications, Knowledge Gap remains in the development of structured social deduction card games specifically adapted to foster speaking confidence in secondary EFL settings. Aims of this study are to design and describe Ray’s Werewolf Social Life Deducting Card-Game as an interactive speaking learning media for high school students. Results indicate that the game structure, consisting of role-based cards, morning and night discussion phases, and persuasive interaction, creates opportunities for spontaneous verbal expression, collaboration, and critical thinking. Preliminary user feedback suggests increased student engagement and motivation during speaking activities. Novelty lies in the pedagogical adaptation of a social deduction card game into a structured EFL speaking medium with simplified English instructions and role-based communicative tasks. Implications suggest that this card-based learning media can serve as an alternative instructional tool to support communicative language teaching and reduce speaking anxiety in secondary education contexts. Keywords: Game-based Learning, EFL Speaking, Learning Media, Social Deduction Game, Speaking Confidence Key Findings Highlights Role-based interaction facilitates spontaneous oral communication in classroom settings. Cyclical discussion phases support collaborative reasoning and verbal argumentation. Card-based design provides structured yet flexible integration into secondary language lessons.